Evaluation of Watermelon (Citrullus lanatus) Juice Preserved with Chemical Preservatives at Refrigeration Temperature (Journal of Scientific Research, 2013)
This study was done to analyze the effect of chemical preservatives on watermelon juice. Ten different samples of pasteurized watermelon juices with different chemical preservatives, termed as T1, T2, T3, T4, T5, T6, T7, T8, T9, T10 , were made which were stored at 4 - 15°C for three months. T1 and T2 were rejected soon due to spoilage. pH decreased from 5.094 to 4.017 and minimum pH content was reduced in T10 (7.87%), while maximum in T1 (57.55%). The total soluble solids (TSS) increased from 17.460% to 18.980% with maximum in T1 (51.67%) and minimum in T7 (4.88%). Reducing sugar was increased from 15.650 to 17.500% with maximum in T10 (18.22%) and minimum in T2 (5.90%).  Minimum microbial load was observed in T10 (0.20cfu/ml) and maximum in T1 (>24 cfu/ml) in case of coliforms; minimum in T10 (78×105 cfu/ml) and maximum in T1 (258×105 cfu/ml) in case of total viable bacteria and same results (minimum in T10 and maximum in T1) were shown in case of fungal count. E.coli was found in T1, T2, T3 and T4 and some bacteria was found in SS agar (especially Salmonella) in T1, T2, T3 and T5. Among all the treated juice samples T10 was most effective in maintaining the sensory and nutritional quality during storage.Keywords: © 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved.doi: http://dx.doi.org/10.3329/jsr.v5i2.12181        J. Sci. Res. 5 (2), 407-414 (2013)